2011
DOI: 10.1007/s13318-011-0027-z
|View full text |Cite
|
Sign up to set email alerts
|

Prediction tacrolimus blood levels based on the Bayesian method in adult kidney transplant patients

Abstract: The use of tacrolimus is complicated by its narrow therapeutic index and wide intra- and interpatient variability. We have previously described a tacrolimus population pharmacokinetics model obtained in an adult kidney transplant cohort. The aims of the present study were (1) to validate that model using an external dataset and (2) to evaluate the prediction using a Bayesian method. Data were retrospectively collected from 34 adult patients receiving kidney transplantation. Trough blood concentrations of tacro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Days post transplant was the most significant clinical factor affecting tacrolimus CL/F and has been previously shown to be associated with CL/F [9,10,[25][26][27].Tacrolimus CL/F decreased by 14% in days 6-10 post transplant and by 29% in days 11-180 post transplant, relative to the immediate post-transplant period (days 3-5). This decrease in CL/F is consistent with previous findings [10,26].…”
Section: Figurementioning
confidence: 91%
See 1 more Smart Citation
“…Days post transplant was the most significant clinical factor affecting tacrolimus CL/F and has been previously shown to be associated with CL/F [9,10,[25][26][27].Tacrolimus CL/F decreased by 14% in days 6-10 post transplant and by 29% in days 11-180 post transplant, relative to the immediate post-transplant period (days 3-5). This decrease in CL/F is consistent with previous findings [10,26].…”
Section: Figurementioning
confidence: 91%
“…Various studies have demonstrated an induction of CYP3A enzymes by corticosteroid therapy [42][43][44]. Although controversial, studies have identified corticosteroid therapy as a significant factor towards tacrolimus CL/F [9,27,[45][46][47]. Clinical practice varies substantially between centres.Therefore, the attribution of the …”
Section: Figurementioning
confidence: 99%
“… proposed a model for initial dosing that was found to be imprecise during external evaluation . Models externally evaluated for Bayesian dose adjustments have been found imprecise in the first weeks post‐transplant . Six of the available models were evaluated for their ability to predict the tacrolimus area under the concentration–time curve in independent patients and were found unacceptably imprecise unless at least two individual concentrations within the dosing interval were known .…”
Section: Introductionmentioning
confidence: 99%
“…Therapeutic drug monitoring (TDM) based on TAC whole blood concentration assessment is commonly used as a marker to prevent ACR. Besides, a pharmacogenetic approach [4] or a dose individualization based on Bayesian models [5,6] or bottom-up approach [7] may be helpful to further optimize the individualization of TAC dosing in liver transplant recipients. However, it is still uncertain whether these two latter approaches have a significant impact on clinical outcome [8,9].…”
Section: Introductionmentioning
confidence: 99%